Pain Across the Menstrual Cycle: Considerations of Hydration - Tan, Beverly; Philipp, Michael; Hill, Stephen; Che Muhamed, Ahmad Munir; Mündel, Toby (Frontiers in Physiology, 2020)
Chronic pain – pain that persists for more than 3 months – is a global health problem and is associated with tremendous social and economic cost. Yet, current pain treatments are often ineffective, as pain is complex and influenced by numerous factors. Hypohydration was recently shown to increase ratings of pain in men, but studies in this area are limited (n = 3). Moreover, whether hypohydration also affects pain in women has not been examined. In women, changes in the concentrations of reproductive hormones across menstrual phases may affect pain, as well as the regulation of body water. This indicates potential interactions between the menstrual phase and hypohydration on pain, but this hypothesis has yet to be tested. This review examined the literature concerning the effects of the menstrual phase and hypohydration on pain, to explore how these factors may interact to influence pain. Future research investigating the combined effects of hypohydration and menstrual phase on pain is warranted, as the findings could have important implications for the treatment of pain in women, interpretation of previous research and the design of future studies.